2008
DOI: 10.1007/s10750-008-9691-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variations of the zooplankton abundance and composition in a West African tropical coastal lagoon (Grand-Lahou, Côte d’Ivoire)

Abstract: Zooplankton constitutes a sensitive tool for monitoring environmental changes in coastal lagoons; however, the available information on zooplankton communities is not sufficient to optimize their rational management. The relationships between zooplankton distribution and environmental factors were studied in a tropical lagoon to test whether the indicator properties of zooplankton assemblages could be used to monitor water quality, in a context of expected eutrophication provoked by an increasing anthropogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
3
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
5
14
3
8
Order By: Relevance
“…The taxonomic composition described in the present work is typical of brackish water zooplankton assemblages (Ferrari et al 1982;Arfi et al 1987;Étile et al 2009). It has also similar characteristics with other Mexican coastal lagoons of the Yucatan Peninsula on the Gulf of Mexico (Chelem lagoon, Escamilla et al 2001;Bojorquez lagoon, Álvarez-Cadena et al 1996;Nichupté lagoon, Álvarez-Cadena et al 2007).…”
Section: Composition and Abundance Of Zooplanktonsupporting
confidence: 58%
“…The taxonomic composition described in the present work is typical of brackish water zooplankton assemblages (Ferrari et al 1982;Arfi et al 1987;Étile et al 2009). It has also similar characteristics with other Mexican coastal lagoons of the Yucatan Peninsula on the Gulf of Mexico (Chelem lagoon, Escamilla et al 2001;Bojorquez lagoon, Álvarez-Cadena et al 1996;Nichupté lagoon, Álvarez-Cadena et al 2007).…”
Section: Composition and Abundance Of Zooplanktonsupporting
confidence: 58%
“…Trophic state is regarded as the most important characteristic of aquatic ecosystem (Andronikova, 1993) and has commonly been found to be important in determining the composition of rotifer communities. However, Etilé et al (2009) has suggested that the role of trophic state in determining the communities of zooplankton including rotifers has not been clearly demonstrated. Among the nutrients related to the trophic state, phosphorus is often a key factor in eutrophication studies as the most common limiting nutrient in freshwater lakes.…”
Section: Introductionmentioning
confidence: 99%
“…Persediaan organisme makanan kelompok zooplankton yang tinggi di perairan diduga menjadi faktor yang mengakibatkan luas relung makanan menjadi rendah (Platell et al, 1998;Hajisamae et al, 2003;Hajisamae and Ibrahim, 2008;Etilé et al, 2009). Ketika pemangsa memanfaatkan mangsa yang berlimpah, luas relung makanan pemangsa tersebut menjadi sempit.…”
Section: Analisa Dataunclassified